Anticholinergic drugs and risk of dementia: Time for action?. Issue 3 (4th June 2021) - Bell, Brian; Avery, Anthony; Bishara, Delia; Coupland, Carol; Ashcroft, Darren; Orrell, Martin
Abstract: Evidence suggests that the prescription of bladder anticholinergics is increasing. Recent studies have accentuated concerns about whether certain prescribed medications could increase risk of dementia, including anticholinergic drugs, and specifically anticholinergics used for bladder symptoms. Nevertheless, it can be difficult to draw together the evidence to review the case for possible causation. Recognising this issue in 1965, Bradford‐Hill set out nine criteria to help assess whether evidence of a causal relationship could be inferred between a presumed cause and an observed effect. In this commentary, we explore the extent to which associations between anticholinergics and dementia satisfy the Bradford‐Hill criteria and examine the potential implications. First, we look at studies that have examined the relationship between anticholinergic drugs with urological properties (bladder drugs) and the onset of dementia, and then present those studies which specifically focus on the cognitive effects of bladder drugs that affect muscarinic receptors in the brain versus the bladder on older people along with suggestions for future research. We also discuss the risks and benefits of these drugs for treating overactive bladder. If it can be shown that certain medications carry a specific risk of dementia, it is possible that initiatives to change prescribing could become a key tool in reducing the risk of dementia and may be easier to implement than some lifestyle changes. Abstract : Given the substantial and increasing prescription of bladder treatment anticholinergics (see Figure 1), it is important to have more clarity regarding the risks of dementia with these drugs. We explore the extent to which associations between anticholinergics and dementia satisfy the Bradford‐Hill and examine the implications. Bradford‐Hill criteria set out nine criteria to help assess whether evidence of a causal relationship could be inferred between a presumed cause and an observed effect. These criteria include the strength of association, consistency in the findings, and biological plausibility. We look at three outcomes in the light of those criteria: (1) The relationship between anticholinergic drugs with urological properties (bladder drugs) and the onset of dementia. (2) The cognitive effects of bladder drugs that affect muscarinic receptors in the brain versus the bladder. (3) The biological mechanisms that may explain the cognitive effects of these drugs. We also discuss the implications for the treatment of patients with bladder symptoms. Conclusions: Oxybutynin satisfies the Bradford‐Hill criteria for establishing a causal link with the development of dementia, which may also be true for other anticholinergics that cross the blood‐brain barrier. We should act now and advise colleagues not to use anticholinergics associated with dementia for bladder symptoms. A deprescribing intervention may reduce the risk of dementia, but we also need to evaluate the possible harm that comes from deprescribing these drugs.